Utilization of Heterologous Siderophores Enhances Levels of Iron Available to Pseudomonas putida in the Rhizosphere - Loper, Joyce E. (American Society for Microbiology, 1999)
Pseudomonas spp. have the capacity to utilize siderophores produced by diverse species of bacteria and fungi, and the present study was initiated to determine if siderophores produced by rhizosphere microorganisms enhance the levels of iron available to a strain of Pseudomonas putida in this natural habitat. We used a previously described transcriptional fusion (pvd-inaZ) between an iron-regulated promoter (pvd) and the ice nucleation reporter gene (inaZ) to detect alterations in iron availability to P. putida. Ice nucleation activity (INA) expressed from the pvd-inaZ fusion by P. putida N1R or N1R Pvd(−), a derivative deficient in the production of a pyoverdine siderophore, was inversely related to the concentration of ferric citrate in a culture medium. In culture, INA expressed by N1R Pvd(−) (pvd-inaZ) was reduced in the presence of the ferric complex of pseudobactin-358, a pyoverdine siderophore produced by P. putida WCS358 that can be utilized as a source of iron by N1R Pvd(−). In the rhizosphere of cucumbers grown in sterilized soil, N1R Pvd(−) (pvd-inaZ) expressed INA, indicating that iron availability was sufficiently low in that habitat to allow transcription of the iron-regulated pvd promoter. Coinoculation with WCS358 or N1R significantly decreased INA expressed by N1R Pvd(−) (pvd-inaZ) in the rhizosphere, whereas coinoculation with a pyoverdine-deficient mutant of WCS358 did not reduce INA expressed by N1R Pvd(−) (pvd-inaZ). These results indicate that iron availability to N1R Pvd(−) (pvd-inaZ) in the rhizosphere was enhanced by the presence of another strain of P. putida that produces a pyoverdine that N1R Pvd(−) (pvd-inaZ) was able to utilize as a source of iron. In culture, strain N1R Pvd(−) also utilized ferric complexes of the siderophores enterobactin and aerobactin as sources of iron. In the rhizosphere of cucumbers grown in sterilized soil, INA expressed by N1R Pvd(−) (pvd-inaZ) was reduced in the presence of strains of Enterobacter cloacae that produced enterobactin, aerobactin, or both siderophores, but INA expressed by N1R Pvd(−) (pvd-inaZ) was not altered in the presence of a mutant of E. cloacae deficient in both enterobactin and aerobactin production. Therefore, the iron status of P. putida was altered by siderophores produced by an unrelated bacterium coinhabiting the rhizosphere. Finally, we demonstrated that INA expressed by N1R containing pvd-inaZ in the rhizosphere differed between plants grown in sterilized versus nonsterilized field soil. The results of this study demonstrate that (i) P. putida expresses genes for pyoverdine production and uptake in the rhizosphere, but the level of gene expression is influenced by other bacteria that coexist with P. putida in this habitat, and (ii) diverse groups of microorganisms can alter the availability of chemical resources in microbial habitats on root surfaces.